EFFISIENSI TEKNIS USAHATANI KEDELAI PADA LAHAN SAWAH DAN DARAT DI KECAMATAN JATIWARAS - Rian Kurnia; Ivan Sayid Nurahman (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Fulfilling the needs of 67.99 percent of soybeans must be imported from abroad. To overcome the deficit in soybean production, the Indonesian government has pursued various soybean development programs. The research was carried out with the aim of: (1) Analyzing the effect of using production factors both simultaneously and partially on soybean farming in Jatiwaras District, Tasikmalaya Regency, (2) Analyzing the technical efficiency of soybean farming in paddy fields and land land in Jatiwaras District, Tasikmalaya Regency. The research method used in this study is an explanatory survey method by taking cases on soybean farming in Jatiwaras District, Tasikmalaya Regency. Samples were taken using Multistage Cluster Random Sampling, then a sample of 127 people was obtained from a population of 185 soybean farmers from two randomly selected villages (Jatiwaras and Papayan Villages), from 11 soybean center villages that planted in rice fields and land agro-ecosystems (Kaputihan, Neglasari). , Sukakerta, Setiawangi, Papayan, Jatiwaras, Ciwarak, Kersagalih, Kertarahayu, Mandalamekar, Mandalahurip). The analysis used for technical efficiency and determining the production factors that directly affect the resulting production output is the Cobb-Douglas stochastic frontier production function. The results of this study indicate that there is one variable that significantly influences the level of soybean production, namely fertilizer, Meanwhile, the variables of land area, seeds, pesticides and labor, meanwhile there are two variables that significantly influence the level of soybean production, namely land area and labor, seeds, fertilizers, and insignificant pesticides. Soybean farmers both on land and rice fields are in stage III (Irrational Stage). The average value of Technical Efficiency (TE) Allocative Efficiency (AE) and Economic Efficiency (EE) in paddy fields is 99.97 TE, 62.68 AE and 62.68 EE while the average values of Technical Efficiency, Allocative Efficiency and Efficiency The economists in rice fields are 21.35 TE, 19.42 AE and 19.42 EE. This value shows that soybean farming on land is more efficient in terms of TE, AE and EE tilapia